The Comparison Of Tracking Methods Using QR Code Marker And Texture Marker On Augmented Reality Application - Bagus Satria; Imron; Mika Debora Br Barus (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
The research entitled " The Comparison Of Tracking Methods Using QR Code Marker And Texture Marker On Augmented Reality Application" aims to build augmented reality-based learning applications, implement tracking methods and then compare QR code markers with texture markers to determine which markers are better in augmented reality. This application displays 3-dimensional virtual objects by utilizing augmented reality technology with the help of the vuforia library, unity 3D software, and blender. Comparison of tracking methods using QR code markers and texture markers based on factors that affect the success of the application in detecting markers/detection objects. These factors are detection angle, detection distance and light intensity. Based on the results of testing on augmented reality applications with tracking methods using QR code markers and texture markers, it is known that QR Code markers can better display 3-dimensional virtual objects based on detection distance and detection angle.